2005
DOI: 10.1002/hed.20197
|View full text |Cite
|
Sign up to set email alerts
|

A case of cervical metastases from temporal bone carcinoid

Abstract: We believe that temporal bone carcinoids have metastatic potential not predictable by histologic features. Surgical excision is the treatment of choice for patients with temporal bone carcinoids, with the approach and technique determined by the extent of the mass. Moreover, before planning surgery and during follow-up, neck node status must be carefully detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 6 publications
2
14
0
Order By: Relevance
“…Even if patients do not complain of any symptoms, patients with carcinoid tumors should be followed up carefully using effective inspection methods. We reviewed 50 cases that described skeletal metastasis from carcinoid tumors (3,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). The characteristics of the reported patients are shown in Table Ⅰ.…”
Section: Discussionmentioning
confidence: 99%
“…Even if patients do not complain of any symptoms, patients with carcinoid tumors should be followed up carefully using effective inspection methods. We reviewed 50 cases that described skeletal metastasis from carcinoid tumors (3,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). The characteristics of the reported patients are shown in Table Ⅰ.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, immunohistochemistry was not done in 16 out of 19 MEA reported cases, which suggests that the percentage of MEA probably represents less than 20% of the cases. Pellini et al presented the only case of middle ear free, temporal bone carcinoid metastasis to the cervical lymph nodes [20]. …”
Section: Discussionmentioning
confidence: 99%
“…In 2005, Pellini et al [18] reported the case of a 55-year-old female with multiple cervical metastases almost 3 years after the diagnosis of a primary carcinoid of the temporal bone. Histologic examination after a modified radical neck dissection was suggestive of lymph node metastases from a carcinoid tumor.…”
Section: Middle Ear Carcinoids With Regional Metastasesmentioning
confidence: 98%